The effectiveness of teaching supported by illuminations in acquiring the concepts of analytic geometry among the tenth grade student and their motivation towards learning mathematics - Alrudaini, Hamed Abdullah Ali; Al-Abed, Adnan Saleem (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to find the effectiveness of teaching supported by illuminations in acquiring the concepts of analytic geometry among the tenth grade student and their motivation towards learning mathematics. To verify this, the researcher prepared a teacher guide for teaching for teaching the unit of analytic geometry and models by illuminations. The researcher has also a test to measure the acquisition of the concepts of analytic geometry and its validity and reliability were checked and verified. The sample of the study consisted of (50) students from tenth grade in AL Batinah North government in the Sultanate of Oman. The sample was divided into two groups. An experimental group and a control group. The experimental group studied the unite of analytic geometry and models using Teaching supported by illuminations. While the control group studied using normal method. The study found the following results: * There is a statically significant difference at the level of significance (α=0.05) between the mean scores of the experimental group students and the control group scores in the post-application of the test of the acquisition of the concept of analytic in favor of the experimental group. * There is a statically significant difference at the level of Significance (α=0.05) between the mean scores of the experimental group students and the control group scores in the post-application of the motivation scale towards Mathematics in favor of the experimental group. Considering these results, the researcher recommended making the best use of the study results and recommendations as well as, the program prepared to apply it. Based on the result of the study which showed the positive effect of illuminations in the acquisition of the concepts of analytic geometry as well as the motivation to wards learning mathematics.